Management Information System for Community Enterprise of Textile group in Nan Province - Hongsibsong, Patcharaporn (Journal of Information and Learning [JIL], 2022)
The objectives of this research were 1) to store and collect data for community enterprises textile group in Nan Province, 2) to develop an information system for data management of cloth community enterprise for community enterprises textile group in Nan Province, and 3) to study users' satisfaction with management information system for community enterprises textile group in Nan Province. A sample of this study were 400 people who were obtained by purposive sampling. Research instruments included Python programming language, MySQL for managing databases, Django, and web development frameworks. Statistics used in data analysis were the mean and standard deviation. The results of the research indicated that the information system for community enterprise information management could work through a web browser with four main functions: 1) data management system, 2) cost calculation system, 3) knowledge of ancient hand-woven fabrics, and 4) reports on the use of information system. System performance in all aspects was at very good level ( =4.55). The results of the user satisfaction were at a very good level ( =4.46). According to the results of the research findings on the efficiency of the system, the system could be used to store data systematically, correctly and precisely as well as to manage the community enterprises efficiently.